How selection affects phenotypic fluctuation - Yoichiro Ito; Hitoshi Toyota; Kunihiko Kaneko; Tetsuya Yomo (Molecular Systems Biology)
Abstract The large degree of phenotypic fluctuation among isogenic cells highlighted by recent studies on stochastic gene expression confers fitness on some individuals through a ‘bet‐hedging’ strategy, when faced with different selective environments. Under a single selective environment, the fluctuation may be suppressed through evolution, as it prevents maintenance of individuals around the fittest state and/or function. However, as fluctuation can increase phenotypic diversity, similar to mutation, it may contribute to the survival of individuals even under a single selective environment. To discuss whether the fluctuation increases over the course of evolution, cycles of mutation and selection for higher GFP fluorescence were carried out in Escherichia coli. Mutant genotypes possessing broad GFP fluorescence distributions with low average values emerged under strong selection pressure. These ‘broad mutants’ appeared independently on the phylogenetic tree and increased fluctuations in GFP fluorescence were attributable to the variance in mRNA abundance. In addition to the average phenotypic change by genetic mutation, the observed increase in phenotypic fluctuation acts as an evolutionary strategy to produce an extreme phenotype under severe selective environments.